Synthesis and in vitro evaluation of novel non-oximes for the reactivation of nerve agent inhibited human acetylcholinesterase. (1st August 2020) - de Koning, Martijn C.; Horn, Gabriele; Worek, Franz; van Grol, Marco
Abstract: Since several decades oximes have been used as part of treatment of nerve agent intoxication with the aim to restore the biological function of the enzyme acetylcholinesterase after its covalent inhibition by organophosphorus compounds such as pesticides and nerve agents. Recent findings have illustrated that, besides oximes, certain Mannich phenols can reactivate the inhibited enzyme very effectively, and may therefore represent an attractive complementary class of reactivators. In this paper we further probe the effect of structural variation on the in vitro efficacy of Mannich phenol based reactivators. Thus, we present the synthesis of 14 compounds that are close variants of the previously reported 4-amino-2-(1-pyrrolidinylmethyl)-phenol, a very effective non-oxime reactivator, and 3 dimeric Mannich phenols. All compounds were assessed for their ability to reactivate human acetylcholinesterase inhibited by the nerve agents VX, tabun, sarin, cyclosarin and paraoxon in vitro. It was confirmed that the potency of the compounds is highly sensitive to small structural changes, leading to diminished reactivation potency in many cases. However, the presence of 4-substituted alkylamine substituents (as exemplified with the 4-benzylamine-variant) was tolerated. More surprisingly, the dimeric compounds demonstrated non-typical behavior and displayed some reactivation potency as well. Both findings may open up new avenues for designing more effective non-oxime reactivators. Graphical abstract: Image 1 Highlights: Synthesis of new Mannich phenol (non-oxime) derivatives. New 4-N-alkylamine derivatives of PADOC show reactivation potential. Mannich phenol dimers show surprising reactivation potential. The results point at potential new avenues for design of non-oximes.